Security in the new millennium : views from South Asia - Basrur, Rajesh M.; Basrur, Rajesh M.; Regional Centre for Strategic Studies (Colombo, Sri Lanka) (New Delhi : India Research Press, 2001)
Contributed articles.
"Regional Centre for Strategic Studies, Colombo."
Keywords: National security -- South Asia